Style wprowadzania zmian - Grzybowska, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Transfonnation, reorganization or restructuring are the creation and change of a whole new form, function or structure of a firm. Transformation or reorganization are to create a company that is better than before. This paper focuses on behaviour within organizations, particulary on the interaction of people, motivation, and leadership. It focuses on the concept of power as it applies to leadership effectiveness. The author presents concepts and techniques necessary to understand organizational behaviour in today's world. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 57-62